REVISITING TRANSLATION IN EFL CLASSROOMS: TEACHERS’ PERSPECTIVES UNDER INDONESIA’S NEW CURRICULUM - Darmawan Budiyanto; Aswadi Jaya; Kurnia Saputri (University of Kuningan, 2026)
This study revisits the role of translation in English as a Foreign Language (EFL) classrooms by examining teachers’ perceptions, experiences, and readiness under Kurikulum Merdeka, Indonesia’s new national curriculum. Fifty English teachers from various secondary schools in Palembang participated in this mixed-method research, which utilized an online questionnaire combining closed- and open-ended items to gather both quantitative and qualitative data. The findings reveal that most teachers perceive translation as an integral component of English instruction, particularly for enhancing students’ writing and reading proficiency. While grammar-oriented translation remains dominant, there is a noticeable shift toward meaning-focused and communicative translation practices aligned with task-based learning. This pedagogical transition reflects teachers’ efforts to reconcile traditional accuracy-based instruction with the communicative emphasis of Kurikulum Merdeka. Despite recognizing translation as a complex and demanding approach, the majority of teachers demonstrate strong willingness to integrate it into their teaching, signifying high professional commitment and openness to innovation. The study highlights that translation-based learning serves not only as a bridge between linguistic knowledge and real-world application but also as a tool for developing intercultural competence and reflective teaching practices. These findings underscore the importance of sustained institutional support and targeted professional development programs to strengthen teachers’ pedagogical competence in translation and ensure effective curriculum implementation within Indonesia’s evolving EFL landscape.